High Temperature Isothermal Oxidation at 950°C of Ni-based Fe-40Ni-24Cr Alloy - A.I. Anuar; N. Parimin; N.A. Ahad; M.N. Derman; S. Garus; P. Vizureanu (Archives of Metallurgy and Materials)
The effect of different heat treatment temperatures on the isothermal oxidation of Ni-based Fe-40Ni-24Cr alloy was studied. The alloy underwent a heat treatment process at 1000°C and 1200°C for 3 hours of soaking time, followed by water quenching. These samples are labeled as N10 and N12. The heat-treated samples were characterized in terms of grain size using an optical microscope and hardness testing using a Rockwell hardness. As a result, increasing the heat treatment temperature increases the average grain size of the alloy and lowers the hardness value. Heat-treated N10 and N12 samples were subjected to an isothermal oxidation test at 950°C for an exposure time of 150 h. Oxidized heat-treated samples were characterized in terms of oxidation kinetics calculated based on weight change per surface area as a function of time. In addition, phase analysis and oxide surface morphology were measured using x-ray diffraction (XRD) and scanning electron microscopy (SEM) techniques. As a result, the oxidation kinetics of both samples showed a pattern of weight gain with N10 recording the lowest weight gain. Both samples obey a parabolic rate law, indicating a controlled oxide growth rate. N10 recorded the lowest parabolic rate constant of 2.5×10–8 mg2cm–4s–1, indicating a low oxidation rate, thus having good oxidation resistance. Phase analysis using XRD shows that several oxide phases have been formed consisting of Cr-containing oxides Cr2O3 and MnCr2O4. In addition, SEM analysis displayed a uniform oxide layer formed on the N10 sample, indicating good oxide adhesion. This finding shows an important contribution to the oxidation protection mechanism that records the fine grain obtained from the heat treatment process can increase good oxidation resistance.